2004
DOI: 10.1111/j.1442-2042.2004.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasonography in evaluation of benign prostatic hyperplasia

Abstract: Background : The clinical application of volume estimation by 3-D ultrasound has recently gained much attention. However, there have been no reports evaluating the prostate volume by 3-D transrectal ultrasound (TRUS) before transurethral resection of the prostate (TURP). The purpose of the present study was to evaluate the value of 3-D TRUS for prediction of prostate morphology and resected weight before TURP and to investigate whether 3-D TRUS is a more useful examination than 2D TRUS in patients with benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…As such, SPUS shows promise as a modality to support modern surgical techniques like TURP for the management of BPH in sub-Saharan Africa. This study found a strong correlation (q = 0.98) between the preoperative volume of prostate using SPUS and TRUS, as in previous studies [5,7,8,[11][12][13][14]. Agreement between modalities was also strong, based on Bland-Altman analysis [10], with zero bias and upper and lower limits of agreement less than ±15 mL.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As such, SPUS shows promise as a modality to support modern surgical techniques like TURP for the management of BPH in sub-Saharan Africa. This study found a strong correlation (q = 0.98) between the preoperative volume of prostate using SPUS and TRUS, as in previous studies [5,7,8,[11][12][13][14]. Agreement between modalities was also strong, based on Bland-Altman analysis [10], with zero bias and upper and lower limits of agreement less than ±15 mL.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, Kanao et al compared the volume of the whole prostate and the weight of the enucleated adenoma on 23 Japanese patients with BPH and found a difference of 21 mL between preoperative prostate volume and volume of enucleated adenoma [13]. Incomplete removal of the adenoma or volume overestimation by ultrasound techniques may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 95%
“…More than 6% of visiting patients with a primary diagnosis of prostatitis have a concomitant diagnosis of BPH. Some older men with LUTS may be incorrectly diagnosed with BPH simply because of their symptoms and their old age, or they may have prostatitis as well as BPH [20]. Recently, there has been much research on this.…”
Section: Discussionmentioning
confidence: 99%
“…This was one of the main ongoing needs for technical developments capable of improving ultrasound image resolution without disturbing real time display. The development has started with the introduction of three‐dimensional ultrasound (3D US) into the imaging field and is particularly robust with the recent advances of dynamic interactive speckle reduction 19–21 …”
Section: Introductionmentioning
confidence: 99%
“…The development has started with the introduction of three-dimensional ultrasound (3D US) into the imaging field and is particularly robust with the recent advances of dynamic interactive speckle reduction. [19][20][21] In the present study, we used Three-Dimensional eXtended Imaging (3D XI) technology, which is a software update of 3D US, as a comprehensive modality to try to correlate symptoms in isolated BPH through characterization of nodular balance alongside the prostatic urethra and the nodular type-dominance in aging men, through which further studies may advance.…”
Section: Introductionmentioning
confidence: 99%